Integrating Mechanisation in Sustainable Agriculutural Development Strategies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The main seminar themes were the agro-ecological and socio-economic conditions conducive to mechanisation, the role of stakeholder groups and the private and public sectors, and networking activities.